Innovations at the intersection of homelessness and substance use during the COVID-19 pandemic: a scoping review - Hannah Passmore; Sam Craft; Rachel Krieger; Sunny Tang; Sofia Sacerdote; Emily Lumbis; Stephanie Blaufarb; Kelly M. Doran (Harm Reduction Journal)
Abstract Background The COVID-19 pandemic led to disruptions in substance use and harm reduction services for people experiencing homelessness (PEH) as well as opportunities to innovate. Pandemic-era innovations may offer insights on more effective approaches to the intertwined issues of homelessness and substance use beyond the pandemic. We present findings from a scoping literature review of articles describing interventions related to substance use and homelessness that emerged during the pandemic. Methods We conducted a scoping literature review to identify articles on pandemic-era innovations related to substance use and homelessness. We completed a comprehensive search for articles in nine academic and grey literature databases in November 2022, and a second database search in September 2023. We screened titles, abstracts, and full text using predefined inclusion and exclusion criteria. We extracted data on study design, location, participants, and outcomes. Results Database searches yielded 812 unique articles; 68 met inclusion criteria. Most articles discussed interventions addressing opioid use (n = 60). Commonly described interventions included telemedicine-based prescribing of medications for opioid use disorder (MOUD), homeless services site-based MOUD provision, managed alcohol programs, supervised consumption services, and safer supply prescribing. Articles reported few intervention-related adverse effects, though study designs (e.g., non-experimental, observational studies lacking comparison groups) presented limitations to effectiveness outcome assessment. Surmountable challenges associated with interventions included inequitable access to technology for PEH. Conclusions Innovations in programs that provide substance use treatment and harm reduction services to PEH were observed during the COVID-19 pandemic. Further evidence is needed to determine which COVID-19 pandemic-related innovations were most impactful and how they should be prioritized and continued post-pandemic.